An exploratory study on ERP adoption in SMEs – a case of Gwalior region in North-Central India. (1st January 2011) - Bhadouria, Megha; Acharya, Padmanav; Singh, Deepali
While the utility of enterprise resource planning (ERP) systems as a means of providing complete business solutions for large firms is well established; the same may not be the case with small and medium enterprises (SMEs). However; that has not deterred many SMEs from developing keenness in implementing ERP systems in their set ups for bringing in an efficient and integrated operation. This paper presents findings of an exploratory study on the factors that influence ERP adoption decision in SMEs based on field study and questionnaire survey and brings in the key factors involved.